Breastfeeding is not related to postpartum relapses in multiple sclerosis - Portaccio, E; Ghezzi, A; Hakiki, B; Martinelli, V; Moiola, L; Patti, F; La Mantia, L; Mancardi, G L; Solaro, C; Tola, M R; Pozzilli, C; De Giglio, L; et al. (Neurology, 2011)
To assess the relationship between breastfeeding and risk of puerperal relapses in a large cohort of patients with multiple sclerosis (MS). We prospectively followed-up pregnancies occurring between 2002 and 2008 in women with MS, recruited from 21 Italian MS centers, and gathered data on breastfeeding through a standardized interview. The risk of relapses after delivery was assessed using the Cox regression analysis. A total of 302 out of 423 pregnancies in 298 women resulted in full-term deliveries. Patients were followed up for at least 1 year after delivery. The time-dependent profile of the relapse rate before, during, and after pregnancy did not differ between patients who breastfed and patients who did not. In the multivariate analysis, adjusting for age at onset, age at pregnancy, disease duration, disability level, and relapses in the year prior to pregnancy and during pregnancy, treatment with disease-modifying drugs (DMDs), and exposure to toxics, the only significant predictors of postpartum relapses were relapses in the year before pregnancy (hazard ratio [HR] = 1.5; 95%confidence interval [CI] 1.3-1.9; p < 0.001) and during pregnancy (HR = 2.2; 95% CI 1.5-3.3; p < 0.001). In our sample, postpartum relapses were predicted only by relapses before and during pregnancy. Therefore, the reported association between breastfeeding and a lower risk of postpartum relapses may simply reflect different patient behavior, biased by the disease activity. Our results can assist neurologists facing the breastfeeding issue in mother counseling and shared decision-making. Especially, among patients with high risk of postpartum relapses, breastfeeding may not be feasible and early postpartum treatment should be an option.